The role of data-driven marketing strategy in sustaining Halal SMEs - Jaiyeoba, Haruna Babatunde; Mohd. Salleh, Hamzah (AIJR Publisher, 2023)
Halal SMEs are often regarded as the engine of economic growth around the world due to their significant contributions to innovation and economy. Despite their impacts, these businesses are faced with enormous challenges in today’s highly competitive environment. To excel in this fierce marketplace, halal SMEs must leverage every available advantage that could contribute to their growth and sustainability. One of such useful tools to adapt quickly to changing market dynamics, compete effectively, and secure longterm success in the marketplace is a data-driven marketing strategy. Thus, understanding the role of this tool has become crucial for these businesses than ever. As such, this study explores the pivotal role of data-driven marketing in sustaining halal SMEs by adopting qualitative research design. Based on this research design, data were collected from 10 academic marketing experts in Malaysia who are also familiar with data analytics. Using thematic analysis, it was discovered that the adopting data-driven marketing strategy can help halal SMEs to make informed decisions, drive customer engagement, and build meaningful connections with the audience. Their ability to use data to create more targeted, effective, and personalised marketing strategies can potentially drive halal SMEs growth and ensure their long-term sustainability. Overall, these findings offer practical implications for halal SMEs regarding the role of data-driven marketing strategies in sustaining these businesses from the perspective of Malaysia.